2022
DOI: 10.1016/j.jds.2021.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of the styloid process in a Taiwanese population using cone beam computed tomography

Abstract: Background/purpose Review of literature, evaluation of the styloid process (SP) using cone beam computed tomography (CBCT) has not been performed in a Taiwanese population. Our study aimed to evaluate the different characteristics of SP using CBCT in a Taiwanese population. Materials and methods CBCT scans of 121 patients (55 males, 66 females; mean age, 27 ± 9.09 years) were evaluated to assess the length, morphological type, calcification pattern, and angulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
(46 reference statements)
5
5
0
Order By: Relevance
“…The mean MLA was significantly greater in males than females (70.4 o and 69.3 o respectively). This was similar to Basekim et al, (16) (70.5° and 68.7°) and Chu et al (34) (67.54° and 66.38°) for males and females respectively. On the contrary, greater values for female subjects were found by Buyuk et al (1) (70.34° and 72.23° for males and females respectively).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The mean MLA was significantly greater in males than females (70.4 o and 69.3 o respectively). This was similar to Basekim et al, (16) (70.5° and 68.7°) and Chu et al (34) (67.54° and 66.38°) for males and females respectively. On the contrary, greater values for female subjects were found by Buyuk et al (1) (70.34° and 72.23° for males and females respectively).…”
Section: Discussionsupporting
confidence: 91%
“…In the whole sample, the mean right MLA was greater than the left (70.3° and 69.1° respectively) which agrees with Ramadan et al (3) and Chu et al (34) . However, Yılmaz et al (33) reported greater MLA values for the left side.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations